2022
DOI: 10.1093/mr/roac070
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for denosumab discontinuation in patients with postmenopausal osteoporosis

Abstract: Objectives Persistence with treatment is key to achieving successful treatment outcomes in patients with osteoporosis. We investigated risk factors for denosumab discontinuation in patients with postmenopausal osteoporosis (PMO). Methods A total of 333 patients with PMO who had never received osteoporosis treatment were included in this study. Baseline demographics and retention rate of denosumab were evaluated in all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Our multicenter study based on real-world data showed that 26.2% of Korean male osteoporosis patients completed 24 months of denosumab treatment. Several prior retrospective studies have been conducted to investigate the persistence with denosumab (Supplemental Table S1) [19][20][21][22][23][25][26][27][28][29][30][31][32][33][34]. However, few studies have explored persistence with denosumab in the male population.…”
Section: Discussionmentioning
confidence: 99%
“…Our multicenter study based on real-world data showed that 26.2% of Korean male osteoporosis patients completed 24 months of denosumab treatment. Several prior retrospective studies have been conducted to investigate the persistence with denosumab (Supplemental Table S1) [19][20][21][22][23][25][26][27][28][29][30][31][32][33][34]. However, few studies have explored persistence with denosumab in the male population.…”
Section: Discussionmentioning
confidence: 99%